Temperature dependence of creep rupture life of long-term serviced Grade 91 steel - Yaguchi, Masatsugu; Kanai, Masayuki; Tamura, Koji (Frontiers in Materials, 2025)
A series of creep tests, which include those under actual service conditions of ultra-super-critical power plants, have been carried out on long-term serviced Grade 91 steels to investigate the temperature dependence of the remaining creep life of the materials. Linear relationships between the reciprocal of absolute temperature and the logarithms of creep rupture life were observed even under actual service conditions. The temperature dependence of creep rupture data was assessed in detail in terms of the constant C in the Larson-Miller parameter. As far as the results obtained in this work, the experimental values of constant C depend negligibly on stress levels and material strength. The values of constant C are between 18 and 21 for base metals and between 16 and 21 for welded joints of Grade 91 steels. These findings indicate that the impact of temperature-dependent deviations on creep life estimation is not pronounced. An estimation method, which we have proposed for short-term data to predict long-term creep life, was applied to the test data, and it was demonstrated through calculations that the estimation method is valid for Grade 91 steels even under actual service conditions.